2020
DOI: 10.3390/pathogens9020110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Genetic Characteristics of Equine Herpesvirus in Korea

Abstract: Respiratory diseases cause significant economic losses (especially in the horse racing industry). The present study describes the detection and genetic characteristics of equine herpesvirus (EHV) from a total of 1497 samples from clinically healthy horses in Korea, including 926 blood samples, 187 lung tissues, and 384 nasal swabs. EHV-2 and EHV-5 were detected in 386 (41.7%; 95% CI: 38.5-44.9) and 201 (21.7%; 95% CI: 19.1-24.4) blood samples, respectively, and in 25 (13.4%; 95% CI: 8.5-18.2) and 35 (18.7%; 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
5
4
0
Order By: Relevance
“…Furthermore, in the current study EHV-4 was not detected among apparently healthy equids. This finding was coincided with previous reports of Negussie et al (2017b) who reviewed that EHV-1 and EHV-4 were never detected among apparently healthyequids and EHVs infection was never detected in apparently healthy donkeysand Seo et al (2020) who elucidated that EHV-4 was not detected in any of the samples evaluated among apparently healthy horses. On the other hand, this re-4869 sult was in contrast to previous reports of Azab et al (2019) who documented that all EHVs were detected in apparently healthy equids.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in the current study EHV-4 was not detected among apparently healthy equids. This finding was coincided with previous reports of Negussie et al (2017b) who reviewed that EHV-1 and EHV-4 were never detected among apparently healthyequids and EHVs infection was never detected in apparently healthy donkeysand Seo et al (2020) who elucidated that EHV-4 was not detected in any of the samples evaluated among apparently healthy horses. On the other hand, this re-4869 sult was in contrast to previous reports of Azab et al (2019) who documented that all EHVs were detected in apparently healthy equids.…”
Section: Discussionsupporting
confidence: 91%
“…Although the ORF30 D752 genotypes (3/55, 5.5%) were reported in 2014 in Korea [ 18 ], this neurological genotype may not be common in Korea. Recently, similar studies were reported in other countries, and the prevalence of the neuropathogenic genotype was extremely low in Japan (2.7%), Australia (3%) and Argentina (7.4%) [ 23 ]. In particular, neuropathogenic cases were extremely rare in Korea [ 16 ].…”
Section: Discussionsupporting
confidence: 55%
“…Unfortunately, limited genetic data are available in Korea. To date, only ORF30 and ORF33 have been analyzed [ 19 , 20 , 23 ]; however, these sequences are not present in databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a zoo, EHV‐1‐positive guinea pigs ( Cavia porcellus ) died after ataxia and paralytic disorders, showing also abortions and stillbirths (Wohlsein et al, 2011). Apparently accidental hosts such as Thomson’s gazelle ( Eudorcas thomson ) (Kennedy et al, 1996; Wohlsein et al, 2011; Guo et al, 2014; Sakaguchi et al, 2017), fallow deer ( Dama dama ) (Kinyili and Thorsen, 1979; Abdelgawad et al, 2016), blackbuck ( Antelopa cervicapra ) and giraffe ( Giraffa camelopardalis reticulate ) have been reported to be infected with EHV‐1 or EHV‐9 (Chowdhury et al, 1988; Borchers et al, 2006; Kasem et al, 2008). EHV‐9 can be also named Gazelle herpesvirus (GHV) (Fukushi et al, 1997).…”
Section: Assessmentmentioning
confidence: 99%